Determination of total fat and fatty acids composition in selected infant formula and follow up formula available in Malaysia - Nasarudin, Nur Atiqah (Universiti Sains Malaysia, 2016)
Infant formula and follow up formula is one of the main nutritional sources for infants and children. In this study, the total fat and fatty acid compositions of infant formula (n=6) and follow up formula (n=6) were analyzed. Fats were extracted using the Folch et al (1957) method. and fatty acid compositions (group and individual) were analyzed by gas chromatography. In infant formulas, saturated fatty acid (SFA) (1.442~20.715%), monounsaturated fatty acid (MUFA) (1.64o~lu.o84%) and polyunsaturated fatty acid (PUFA) (60.345-73.065%) were the major group of fatty acids detected. Follow up formula products contained 2.319-26.321% of total SFA content, whereas the content of MUFA and PUFA ranged from 0.712-17.774% and 44.258-91.406% respectively. In addition, the range of DHA in infant and follow up formula were 3.487-6.084% and 0.516-15.373% respectively. About 1.624- 4.456% of linoleic acid/linolenic acid was detected in the analyzed products (infant and follow up formula). A small amount of trans fatty acids (2.626-10.144%) were also detected in both infant anf follow up formula.